UPAYA NON GOVERNMENTAL ORGANIZATION SMILE TRAIN DALAM MENGATASI MASALAH KESEHATAN ( BIBIR SUMBING) DI INDONESIA TAHUN 2014 – 2015 - Hany Meiyana; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The methodology of this research was used contemporary study which analysed about efforts which had done by international governmental organization of Smile Train to overcome the problems of harelip in Indonesia. The harelip as a physical defect which was a load born handicap that most happened in develop countries that millions children were suffered as harelip that they could not speak and eat properly. Jagged was happened while middle soft net could not firmly united while the fetus still in process of develop. Jagged can be involved mouth, palates of mouth and soft net at the back mouth of children that they were suffered physically and psychologically. Although many children who were suffered as harelip could not be tackled such as harelip treatment and surgical operation. This was happened because economy factor, poverty factor also uneducated or a little knowledge as well as wrong information about birth with the cleft lip. This research used conceptual background related to International organization of analysis level, this organization has many members from different countries in the world and supporting with theory of actor and analysis level of international organization, this concept directed to qualitative method and librarian research as information resources. Many efforts have done by NGO Smile Train in Indonesia, through medical procedure and therapy, such as free operation of harelip, oral therapy and medical care around mouth and teeth. Through endeavor program to local doctors such as training for profession of medical workers, by supporting medical stuffs and technology, by supporting local communities program, by giving education to the people, and looking for people who were suffered harelip in the remote places, Indonesia and giving financial to the people who were suffered harelip.Keywords: Jagged, Harelip, Smile Train, Effort, Program